The “Endothelialized Muscularis Mucosae”: A Case Report Describing a Large Cavernous Hemangioma at the Terminal Ileum and a New Histologic Clue for Preoperative Diagnosis from Endoscopic Biopsy - Erin K. Purdy-Payne; Jean F. Miner; Brandon Foles; Tien-Anh N. Tran (Case Reports in Gastrointestinal Medicine)
Cavernous hemangiomas of the gastrointestinal tract are quite rare and, until now, have been difficult to diagnose preoperatively due their nonspecific presentations and imaging features, as well as a lack of histologic description pertaining to small superficial biopsies such as those obtained endoscopically. We report a unique case of a 4 cm transmural cavernous hemangioma in the terminal ileum with literature review and describe a new histologic finding—the “endothelialized muscularis mucosae,” which was discovered upon review of the endoscopic biopsy and could potentially facilitate preoperative diagnosis of these lesions from endoscopic biopsies in the future. These lesions have classically required surgical resection in order to make a definitive diagnosis and rule out malignancy, with which they share many historical and radiographic features. Due to their potential to cause bowel obstruction, intussusception, perforation, and hemorrhage, these lesions may ultimately require surgical resection to relieve symptoms or prevent or treat complications—however, surgical planning and patient counseling could be greatly improved by a preoperative diagnosis. Therefore, gastroenterologists, pathologists, and surgeons should be aware of the “endothelialized muscularis mucosae” which can be very helpful in diagnosing GI cavernous hemangiomas from endoscopic biopsies.